The explanation and effectiveness of intellectual and behavioral components in satisfying the lives of married women - Ghashghayi, Akram; Farahbaksh, Kiomarth; Shariatmadar, Asieh; Moatamedi, Abdollah (Novelty in Biomedicine, 2019)
Background: The aim of this study was to determine the components of the educational model of intellectual and behavioral principles in healthy interpersonal relationships based on the Holy Quran and its effectiveness on marital satisfaction of married women. Research was arranged in two sections. Materials and Methods: The research method was qualitative in the first part and was quantitative in the second part. In the qualitative section, after researching and searching in the sources of the Quran, which was carried out by a qualitative method in the form of thematic analysis, ultimately the intellectual and practical principles in the healthy interpersonal relations based on the Holy Quran were determined and explained. The method of the second part of the research is quantitative and of type Semi-experimental, with pre-test-posttest design with control group and random selection. For this purpose, 30 married women with children from Tehran selected in a sample of 30-97 years old and randomly assigned to two groups of 15 subjects. The instrument of this research was a survival satisfaction questionnaire (SWIS). The experimental group was placed under the training of the principles of intellectual and behavioral training in healthy interpersonal relationships based on the Holy Qur'an for two months. Results: The results of the hypothesis test showed that the components of the educational model of intellectual and behavioral principles in healthy interpersonal relationships based on the Holy Quran On the other hand, life satisfaction variable (83.36, F=0.001) had a significant effect. This power is 100%. In other words, there was a significant difference between the experimental group and the control group in terms of the variables. Conclusion: In explaining this finding, it could be said that the sacred religion of Islam in various aspects of family life has provided useful commands and teachings. In Islamic religion, marriage and family are declared the most beloved and dearest human institution to God, and the adoption of these orders can affect the satisfaction of couple’s life.